2018
DOI: 10.18608/jla.2018.51.5
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence Data Model for Analyzing Temporal Patterns of Student Data

Abstract: Data models built for analyzing student data often obfuscate temporal relationships for reasons of simplicity, or to aid in generalization. We present a model based on temporal relationships of heterogeneous data as the basis for building predictive models. We show how within- and between-semester temporal patterns can provide insight into the student experience. For example, in a within-semester model, the prediction of the final course grade can be based on weekly activities and submissions recorded in the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
16
0
3
Order By: Relevance
“…This illustrates that even relatively limited institutional data (records of course outcomes for student-course pairs) can potentially provide a wealth of information about students, courses, and majors. Similarly, Mahzoon et al (2018) focused on information contained in sequences of student course outcomes to build sequential descriptors of student academic performance across terms from college entrance to graduation, providing a basis for visualizations and automatically generated narratives about student trajectories. This approach derived sequential signatures for each student to predict on-time graduation, concluding that temporal information as a student progresses through college is important in predicting student outcomes.…”
Section: Course Guidance and Information Systemsmentioning
confidence: 99%
“…This illustrates that even relatively limited institutional data (records of course outcomes for student-course pairs) can potentially provide a wealth of information about students, courses, and majors. Similarly, Mahzoon et al (2018) focused on information contained in sequences of student course outcomes to build sequential descriptors of student academic performance across terms from college entrance to graduation, providing a basis for visualizations and automatically generated narratives about student trajectories. This approach derived sequential signatures for each student to predict on-time graduation, concluding that temporal information as a student progresses through college is important in predicting student outcomes.…”
Section: Course Guidance and Information Systemsmentioning
confidence: 99%
“…In this work, we describe a methodology for the study of time-series data collected from the engagement of learners with the tasks and stages of online courses. The analysis of temporal statistics has been shown to provide a fruitful avenue to identify learners at risk of failure, 3 predicting performance, 4 dropping out of a course, 5–8 or identifying learner behaviours. 9 Despite such developments, a recent review of the field suggested that temporal analyses are currently insufficient in number, and that additional methodologies are required.…”
Section: Introductionmentioning
confidence: 99%
“…This is why in most learning analytics studies, the effect of time is obfuscated or ignored. There have been proposals to model these effects correctly (Mahzoon et al, 2018). As the level of analytic tools available remains quite small, the impact of these models is also small.…”
Section: Learning Analytics and Learning Picturesmentioning
confidence: 99%